AN ANALYSIS OF STUDENTS READING COMPREHENSION ON RECOUNT TEXT AT SMK DHARMA BAKTI 1 MEDAN - Hutagalung, Febri Nila Rosaria; Hutagalung, Dervine; Simanjuntak, Dinaria Veronika; Yanti Tampubolon, Putri Delima (Jurnal Ilmiah Mandala Education (JIME), 2021)
ABSTRACTThis research was conducted to describe the students' ability to read and understand the Recount Text. The purpose of this study was to analyze the students' ability in understanding the Recount Text. This research used descriptive qualitative method. This research was conducted at SMK Dharma Bakti 1 Medan. The sample of this research was 17 students of class 10 TKJ. This study used a reading test and interview instruments. Based on the research results, it was found that the highest score of students was 73.00 and the lowest score of students was 6.00. The low score of students caused by the lack of understanding of students in reading recount text and limited vocabulary of students.Keywords: Students’ analysis, reading comprehension, recount textABSTRAK Penelitian ini dilakukan untuk mendeskripsikan kemampuan siswa dalam membaca dan memahami Teks Recount. Tujuan penelitian ini adalah untuk menganalisis kemampuan siswa dalam memahami Teks Recount. Penelitian ini menggunakan metode kualitatif deskriptif. Penelitian ini dilakukan di SMK Dharma Bakti 1 Medan. Sampel penelitian ini sebanyak 17 siswa kelas X-TKJ. Penelitian ini menggunakan instrumen tes membaca dan wawancara. Berdasarkan hasil penelitian, ditemukan skor tertinggi siswa adalah 73,00 dan skor terendah siswa adalah 6,00. Rendahnya nilai siswa disebabkan oleh kurangnya pemahaman siswa dalam membaca teks recount serta kosakata yang dimiliki siswa terbatas.kata kunci : Analisis siswa , pemahaman membaca, teks recount